Zero Identity — The New Cybersecurity Paradigm - Ronhaar Wayne; Zehner William Bradley; Langhorne Robert (Marketing of Scientific and Research Organizations, 2021)
Global cybercrime is exploding geometrically. The traditional methods of securing cyber systems via complex passwords frequently fail, exposing the computer systems to many types of cybercrimes. Cybercrime of all kinds is a growing concern for individuals, government and business organizations, and society. Zero Identity is a new technology that “bubbles, cloaks, and hides” computers and their contents from cybercriminals. Zero Identity is a mature and proven military-based technology with over a 20-year history. Cylentium, a cybersecurity startup, is adapting Zero Identity technology to consumers and civilian organizations. Market and technological acceptance of Zero Identity may lead to a cybersecurity paradigm shift in the next decade. This paper explores the history of Zero Identity, what it does, how it works, and its future prognosis. One of the original developers (Rob Langhorne) of the Zero Identity concept was interviewed, as was the concurrent entrepreneur (Wayne Ronhaar). Both Langhorne and Ronhaar became coauthors of this article to contribute their first-hand historical perspectives, challenges, and insights to transform technology into a commercial product in a series of articles.